“Moral Electricity”: William Daniell’s Voyage Round Great Britain and Early Topographical Representations of the Isle of Skye and the West Highlands - Leask, Nigel (Romanticism on the Net, 2022)
This essay addresses visual and letterpress representations of the West Highlands and Islands in William Daniell’s Voyage Round Great Britain (1814–25), a patriotic celebration of the defensive coastal ramparts that had protected the nation from Napoleonic invasion. It describes Daniell’s career as an aquatint artist in India, his travels round Britain’s coast “sailing on horseback,” and the relationship between the plates and the letterpress text in relation to contemporary topographical art. The essay then turns to Daniell’s travels in the West Coast of Scotland in 1815, contrasting his georgic view of coastal improvements with the socioeconomic crisis afflicting the Scottish Gàidhealtachd in the postwar period. The influence of Thomas Pennant’s artist Moses Griffith, and of Walter Scott’s poetry and Pharos cruise are considered in relation to Daniell’s visual representation of Hebridean coastal scenery, and his notion of “moral electricity,” the transport revolution that has galvanised the nation. Daniell’s evasive account of Highland sheep clearances, and his dedication of his fourth volume to the Marchioness of Stafford, are compared with the critical strictures of earlier travellers like Pennant and Johnson. A final section considers a change in tone in which Daniell’s georgic idiom of improvement is replaced with the aesthetics of the sublime in his representations of “the lakes of terror” Lochs Scavaig and Coruisk in Skye. Owing a large debt to Scott’s Lord of the Isles, these images of the loch and mountain sublime serve to inculcate a disciplined, imperial masculinity. Daniell’s aquatints with their accompanying text provide important insights into the importance of Scotland’s coasts for early nineteenth-century improvement, as well as foreshadowing some of the ambivalent social, economic and environmental consequences that followed.